Arterial cannulation with ultrasound: clinical trial protocol for a randomised controlled trial comparing handheld ultrasound versus palpation technique for radial artery cannulation - Valerie Lan-Pak-Kee; Gareth L. Ackland; Timothy C. Egan; Tom EF. Abbott; Fatima Elsheikh; Stephen Barrett; Mevan Gooneratne; Shaun Montagu May; Matthew Mitchard; Timothy O'Neill; Jennifer Overend; Tom EF. Abbott; et al. (BJA Open, 2022)
Background: Early intraoperative hypotension is associated with acute kidney and myocardial injury in patients undergoing noncardiac surgery. Precise arterial blood pressure measurement before and during the induction of general anaesthesia may avert early intraoperative hypotension. However, rapid arterial cannulation in anxious, conscious patients can be challenging. We describe the protocol for a randomised controlled trial designed to test the hypothesis that readily available, handheld ultrasound-guided arterial cannulation is the optimal method in conscious patients undergoing noncardiac surgery. Methods: Participants >45 yr undergoing noncardiac surgery expected to last >120 min and requiring an overnight hospital stay will be eligible. We will randomly allocate participants to undergo cannulation of the radial artery in the non-dominant arm before the induction of general or regional anaesthesia using either handheld ultrasound-guided dynamic needle position technique or palpation. The primary outcome is first-pass successful arterial cannulation, analysed by intention-to-treat. Secondary outcomes include adequacy/characteristics of the arterial waveform and complications within 24 h of cannulation. We will require 118 patients to demonstrate a doubling of successful first-pass arterial cannulation, from ∼30% using the palpation approach (α=0.05; 1–β=0.1). Results: This study has been approved by the NHS Health Research Authority and Health Care Research Wales (21/WA/0403) and commenced recruitment in May 2022. Conclusions: This study will establish whether handheld ultrasound-guided arterial cannulation before the induction of anaesthesia should be the standard of care in patients at risk of developing perioperative organ injury after noncardiac surgery. Clinical trial registration: NCT05249036.